Financial incentives for private land conservation in the United States - Vana, Jordan, speaker; Dry, Gert, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Americans have supported private land conservation for more than 30 years. In that time, the nation's 1,700 land trusts have helped landowners conserve more than 47 million acres of farm and ranch land, wildlife habitat, and open space around the country, including more than 1.2 million acres in Colorado. Financial incentives play a critical role in these efforts. This session will provide an overview of these incentives, including federal, state and local tax benefits available to conservation-minded landowners, as well as government and private funding options. This session is not intended to provide legal, financial or accounting advice. Rather, it will give participants a working knowledge of the financial incentives available for conservation in the United States, with a particular focus on Colorado.
Moderator: Gert Dry.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses